The Effect of Group Cognitive Behavior Therapy on Behavior Changes in Adolescents Risked of Drug Abuse in Dharmasraya Regency: Pengaruh Terapi Perilaku Kognitif Kelompok terhadap Perubahan Perilaku pada Remaja Berisiko Penyalahgunaan NAPZA di Kabupaten Dharmasraya - Wisdia Lola Erwinda; Susmiati; Heppi Sasmita (Fakultas Keperawatan Universitas Andalas, 2019)
Various problems in adolescents are increasing nowadays, one of them is drug abuse. Considering the condition of Dharmasraya Regency, which is vulnerable to drug trafficking, a prevention act to drug abuse behavior among adolescents is required. This study aimed to determine the effect of Group Cognitive Behavior Therapy (GCBT) on behavior changes in adolescents risked of drug abuse in Dharmasraya Regency. This study design was a Quasi Experimental Research with Pretest and Posttest With Control Group. The samples were 64 people consisting of 32 people in the control group and 32 people in the intervention group. The results of this study indicated that there was a significant influence on behavior changes in adolescent in the intervention group. Meanwhile, there was no significant differences happened in the control group. Therefore, (GCBT) can be applied to change the behavior of adolescents risked at drug abuse. It is expected that GCBT can be implemented at schools in collaboration with the health department to prevent drug abuse on adolescents.